2006
DOI: 10.2214/ajr.05.0695
|View full text |Cite
|
Sign up to set email alerts
|

Opposed-Phase MRI for Fat Quantification in Fat-Water Phantoms with 1H MR Spectroscopy to Resolve Ambiguity of Fat or Water Dominance

Abstract: The fat fraction calculated with opposed-phase imaging (FF(OPI)) and that calculated with 1H MRS (FF(MRS)) correlated well with the known fat fractions of the phantoms (FF(P)): r = 0.99 for FF(OPI); p < 0.0001 and r = 0.96-0.98 for FF(MRS); p < 0.001, for observers 2 and 3, respectively. Opposed-phase imaging should be combined with 1H MRS to ensure accurate quantification of the fat fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 15 publications
0
34
0
4
Order By: Relevance
“…With MR spectroscopy, on the other hand, data are collected in the absence of a gradient, such that the frequency content of the observed signal reflects the native precessional frequencies of various chemical moieties-water (H 2 O), fat (eg, CH 2 ), and others. In effect, MR spectroscopy directly measures the chemical composition of tissue on the basis of the frequency composition of the signal arising from the voxel of interest (15,16).…”
Section: Mr Spectroscopymentioning
confidence: 99%
“…With MR spectroscopy, on the other hand, data are collected in the absence of a gradient, such that the frequency content of the observed signal reflects the native precessional frequencies of various chemical moieties-water (H 2 O), fat (eg, CH 2 ), and others. In effect, MR spectroscopy directly measures the chemical composition of tissue on the basis of the frequency composition of the signal arising from the voxel of interest (15,16).…”
Section: Mr Spectroscopymentioning
confidence: 99%
“…NAFLD is now considered amongst the most concerning liver conditions in children and adults in developed and developing nations (7), and may lead to subsequent development of inflammation and fibrosis in a subset of individuals. With known inherent ambiguity of fat quantification on opposed-phase MRI (8), there is impetus to investigate the continued potential of MRS techniques. Single-voxel 1 H MRS provides localized investigation of water and lipid species in liver, even when lipid amounts are low and difficult to distinguish above noise on MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations of hepatic MRS have transcended initial reports documenting its feasibility as a useful examination method of lipid content (1, 9), and evolved into a technique often used as a standard of reference against newly-developed advanced MRI acquisitions (4, 8, 10). Even though these latter studies report significant correlation with MRS, there are several inherent factors affecting the accuracy and reproducibility of lipid% measurements with MRS, such as field homogeneity, partial volume effects, physiologic motion, and signal decay due to relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on phase differences in images acquired via different TEs, lipid and water signals are additive on in-phase images and subtracted on opposed-phase images [2]. This technique has been proved to be extremely useful for characterization of lesions and organs with fatty components and has gained widespread acceptance [36].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, it is widely used to diagnose lipid-poor adrenal adenomas [3, 7]. On the same bias, chemical shift MR imaging has been used to evaluate vertebral bone marrow fat content in osteoporosis or in distinguishing benign and malignant causes of vertebral bone morrow infiltration [2, 4, 716]. Furthermore, some investigators measured the signal intensity index (SII) value to avoid the problem of signal intensity variability produced by the reference tissue, and found that it appeared to be the most reliable method for differentiating adenomas from non-adenomas [7, 17].…”
Section: Introductionmentioning
confidence: 99%